Marine Botany of the Kenya Coast 3. General account of the environment, Flora and vegetation - Isaac, W. E.; Isaac, F. (J. E. Afr. Nat. Hist. Soc., 1968)
Gives information on the environment of the Kenyan Coast, algal flora and the mangrove vegetation.
All species have been entered except the mangroves.